WHAT MOTIVATED MONOPHYSITE REVOLTS IN THE BYZANTINE EMPIRE? - Jantassov, Amiren (School of Sciences and Humanities, 2022)
For specialists interested in the history of the Roman Empire, it is very interesting to learn about conflicts within the empire because this sheds a light on the history of Rome more comprehensively. Many specialists are interested in the reasons for the aggrandizement and decline of the Roman Empire. Monophysite Christianity is interesting because its conflict with Chalcedonian Christianity caused various rebellions and discontent destabilizing the Eastern Roman (Byzantine) Empire. The struggle between Chalcedonian and anti-Chalcedonian Christianity is an important topic for me as a historian because it allows analyzing the history of the late Roman Empire from different perspectives. This dissertation will mostly focus on the history of the Eastern Roman (Byzantine) Empire. The main authors on whose sources I will rely are John Rufus, Theophanes the Confessor, and Zachariah of Mitylene. John Rufus was a Monophysite monk, who wrote a lot about Monophysite resistance in Palestine. Theophanes the Confessore was a historian and monk, but his position towards Monophysite Christianity is unclear because he has an unclear position towards eunuchs, who are connected with Monophysite Christianity. Zachariah Of Mitylene was a Monophysite historian. Opposition to the center in the monastic community, the struggle of more democratic urban classes, separatism of Eastern nations, and manipulations in the court all have a common element, the connection with Monophysite Christianity. To understand better their ties with Monophysite Christianity I need to say about how Monophysite Christianity motivated the struggle of the groups mentioned above. The study of these facets allows us to understand what really motivated the anti-Chalcedonian revolts. The Monophysite and Chalcedonian divide was strong enough to allow grievances of opposition to center in monastic community and struggle of more democratic urban classes come to the surface, whilst these factors with separatism of Eastern nations and political intrigues (in which eunuchs were involved) also motivated the Monophysite rebellions.
Keywords: Type of access: Restricted; Monophysite revolts; Byzantine Empire